2022
DOI: 10.1111/aec.13209
|View full text |Cite
|
Sign up to set email alerts
|

Variation in thermal and hydrotime requirements for seed germination of Chaco seasonally dry forest species in relation to population environmental conditions and seed mass

Abstract: Thermal and hydrotime requirements for seed germination can vary with the species, environment in which the seeds developed and/or seed mass. We investigated seed germination responses to temperature and water potential of Aspidosperma quebracho-blanco, Bulnesia retama, Parasenegalia visco, Parkinsonia praecox and Tecoma stans, all of which are native tree species of Chaco seasonally dry forests in northwest Argentina. We determined inter-and intraspecific variability in seed germination through thermal and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…For the other species, the low germination percentage in all light and temperature conditions indicates the presence of seed dormancy and the requirement for exposure of seeds to specific environmental conditions to promote dormancy-break and germination. Similar results have been reported for these species and other species characteristic of the seasonally dry Chaco forests of Argentina [38,40]. This interspecific variation in seed traits and seed germination…”
Section: Seed Traits and Seed Dormancysupporting
confidence: 89%
See 3 more Smart Citations
“…For the other species, the low germination percentage in all light and temperature conditions indicates the presence of seed dormancy and the requirement for exposure of seeds to specific environmental conditions to promote dormancy-break and germination. Similar results have been reported for these species and other species characteristic of the seasonally dry Chaco forests of Argentina [38,40]. This interspecific variation in seed traits and seed germination…”
Section: Seed Traits and Seed Dormancysupporting
confidence: 89%
“…In our study, we also found high intraspecific variability in seed traits and seed dormancy and seed germination. Except for P. praecox and S. lorentzii, the study species exhibited intraspecific variability in most seed traits, probably due to a high phenotypic plasticity [12,38,43]. For seeds of S. mistol and S. lorentzii, (with PD), the response to dry storage differed among populations, which may be associated with differences in the intensity of PD and/or sensitivity to dormancy-breaking factors [18].…”
Section: Seed Traits and Seed Dormancymentioning
confidence: 89%
See 2 more Smart Citations
“…One major environmental element that can control enzyme activity and either stimulate or prevent the generation of hormones that influence seed germination is temperature [ 15 , 19 , 20 , 21 ]. The germination responses of seed lots to temperature can be characterized through three cardinal temperatures [ 22 , 23 ]: a base temperature ( T b ), below which the seeds do not germinate; an optimal temperature ( T o ), at which the process proceeds at its fastest pace; and a ceiling temperature ( T c ), above which the process is stopped [ 24 , 25 , 26 ]. These cardinal temperatures, T b , T c , and T o , are associated with the range of ecological and geographic circumstances to which a particular species has evolved, and serve to couple the timing of germination with favorable conditions for subsequent growth and development [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%